Peer Effects on Vocabulary Knowledge: A Linear Quantile Mixed-Modeling Approach - Jamie M. Quinn; Jessica Sidler Folsom; Yaacov Petscher (MDPI AG, 2018)
Do your peers in the classroom have an effect on your vocabulary learning? The purpose of this study was to determine if group-level peer characteristics and group-level peer achievement account for individual-level differences in vocabulary achievement using a large sample of students in kindergarten through second grade (n = 389,917). We applied a mixed-modeling approach to control for students nested among peers, and used quantile regression to test if group-level peer effects functioned similarly across the range of conditional student ability in vocabulary knowledge. Group-level peer effects were more strongly related to vocabulary achievement for students at the low end of the conditional distribution of vocabulary. The difference in vocabulary achievement between children with and without an individualized education program increased as quantiles of the conditional vocabulary distribution increased. Children with lower relative fall scores had better spring scores when they were in homogenous classrooms (i.e., their peers had similar levels of achievement). The importance of classroom composition and implications for accounting for peer effects are discussed.